Recitation: An Alternative Method For Virtual Nahwu Learning - Frida Akmalia; Khoirul Faizin (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
This research is based on the learning state that requires maximum learning even during the pandemic. The researchers assume that the recitation method in virtual nahwu learning can be used to overcome this problem. Then the researchers conducted an initial study, observation, and conducted experiments in a particular class. With observation, the researchers can examine the implementation of virtual nahwu learning. Whereas with experiments, the researchers found that this method is very relevant and could be an option for virtual nahwu learning at STAI Attanwir. It is evidenced by the results of the experimental class's average values before using this method were 67.94 (experimental) and 66.93 (control). After applying the learning method, it was found that the average value was 85.2 for the experimental group and 74.7 for the control group. This result is helpful as an illustration of the virtual Nahwu learning method and a reference for future researchers.